Post-thrombotic syndrome in patients treated with rivaroxaban or enoxaparin/vitamin K antagonists for acute deep-vein thrombosis - Cheung, Y. Whitney; Middeldorp, Saskia; Prins, Martin H.; Pap, Akos F.; Lensing, Anthonie W. A.; ten Cate-Hoek, Arina J.; Villalta, Sabina; Milan, Marta; Beyer-Westendorf, Jan; Verhamme, Peter; Bauersachs, Rupert M.; Prandoni, Paolo; on behalf of the Einstein PTS Investigators Group (Thrombosis and Haemostasis, 2016)
Post-thrombotic syndrome (PTS) is a common complication of deepvein thrombosis (DVT). Poor quality treatment with vitamin K antagonists (VKA) is a risk factor for PTS. We hypothesised that treatment with the direct oral anticoagulant (DOAC) rivaroxaban may lower PTS incidence as compared to enoxaparin/VKA, as DOACs have a more stable pharmacologic profile than VKA. We performed a post-hoc subgroup analysis of the Einstein DVT trial (n=3449). Kaplan-Meier survival analysis was performed to compare the cumulative incidence of PTS between the rivaroxaban and enoxaparin/VKA groups. Hazard ratios (HR) and 95 % confidence intervals (CI) were calculated using Cox proportional hazards models. We included 336 patients with a mean age of 58 ± 16 years and a median follow-up after index DVT of 57 months (interquartile range 48–64). Of these, 162 (48 %) had been treated with rivaroxaban and 174 (52 %) with enoxaparin/VKA. The cumulative PTS incidence at 60 months follow-up was 29 % in the rivaroxaban group and 40 % in the enoxaparin/VKA group. After adjusting for age, gender, body mass index, previous VTE, ipsilateral recurrent DVT, extent of DVT, idiopathic DVT, duration of anticoagulant treatment, compliance to assigned study medication, elastic compression stocking use and active malignancy, the HR of PTS development for rivaroxaban was 0.76 (95 % CI: 0.51–1.13). In conclusion, treatment of acute DVT with rivaroxaban was associated with a numerically lower but statistically non-significant risk of PTS compared to enoxaparin/VKA treatment. The potential effect on reducing PTS deserves evaluation in a large randomised trial.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Post-thrombotic syndrome; rivaroxaban; vitamin K antagonists; deep-vein thrombosis